Comparative Evaluation of Neuroprotective Activity of Tryptanthrin and Its Oxime in Middle Cerebral Artery Occlusion in Rats; Bulletin of Experimental Biology and Medicine; Vol. 177, iss. 3 - Chernysheva; Smol’iakova V. I. Vera Ivanovna; Plotnikov M. B.; Ulyakhina O. A.; Osipenko A. N. Anton Nikolaevich; Kovrizhina A. R. Anastasia Ruslanovna; Khlebnikov A. I. Andrey Ivanovich (2024, 2024)
Title screen